(untitled) (Research, Society and Development, 2022)
Objective: To analyze systematic reviews that evaluated the efficacy and safety of resistance training in women after breast cancer surgery. Methodology: A bibliographic search was performed in Medline, CINAHL, Web of Science, Scopus, PEDro, and Cochrane Library databases, using the RAYYAN (Intelligent Systematic Review) program. The methodological quality and risk of bias in the systematic reviews found were evaluated using the AMSTAR 2 and ROBIS tools. Results: None of the reviews showed an increase in lymphedema volume or an increased risk of developing it with the practice of resistance exercises after breast cancer treatment. Five systematic reviews were found, achieving critically low global confidence. In ROBIS, three reviews were rated as high risk of bias and two as low. Conclusion: Patients with or at risk of developing lymphedema can safely perform resistance exercises and may present benefits in quality of life and muscle strength, without adverse effects of their practice.